Your first week with React - Wanyoike, Michael; Perna, Maria Antonietta; Jelisejevs, Pavels; Laughlin, Chris; Greene, Eric; Brown, Mark; Reyes, Camile (SitePoint Pty., 2017)
React is a remarkable JavaScript library that' taken the development community by storm. In a nutshell, it's made it easier for developers to build interactive user interfaces for web, mobile and desktop platforms. One of its best features is its freedom from the problematic bugs inherent in MVC frameworks, where inconsistent views is a recurring problem for big projects. Today, thousands of companies worldwide are using React, including big names such as Netflix and AirBnB. React has become immensely popular, such that a number of apps have been ported to React -- including WhatsApp, Instagram and Dropbox. This book is a collection of tutorials, selected from SitePoint's React Hub, that will guide you through your first days with the amazingly flexible library.